The gender equation in schools how to create equity and fairness for all students - Ablin, Jason (New York Routledge, Taylor & Francis Group, 2022)
This compelling book takes you inside a teacher's journey to explore the question of gender in education. Jason Ablin uses his background in math teaching, school leadership, and neuroscience to present expert interviews, research, and anecdotes about gender bias in schools and how it impacts our best efforts to educate children. He provides practical takeaways on how teachers and leaders can do better for students. There is also a handy Appendix with step-by-step guides for facilitating faculty-wide conversations around gender; writing learning reports without gender bias; using student assessments to check gendered attitudes about learning; evaluating learning spaces; and creating an inquiry map of your classroom. As a teacher, administrator, DEI director, or homeschooling parent, with the strategies and stories in this book, you'll be ready to embark upon your own journey to balance the gender equation and create greater equity for all of your students"--
Includes bibliographical references.
Keywords: Educational equalization -- United States; Sex discrimination in education -- United States -- Prevention